Evaluation of vegetative and generative characteristics of some ‘Gala’ cultivars - Csihon, Ádám (Acta Agraria Debreceniensis, 2015)
The aim of this study was to evaluate the production characteristics of new ‘Gala’ apple cultivars (‘Gala Venus Fengal’, ‘Gala Decarli- Fendeca’, ‘Galaval’, ‘Jugala’, ‘Gala Schnitzer (S) Schniga’), which can be described with superior and earlier fruit surface coloration and with larger fruit size comparing with the origin cultivar, however they are less well known in our country. The place of our experimental is located in the Nyírség representing adequately the ecological conditions of the surrounding areas, so the gained results can be easily adapted in the biggest apple production site of Hungary. According to the results it can be stated that among the 3–4 years old ‘Gala’ trees, which will achieve the maximal yields just in the next years regarding yields the ‘Fengal’ and the ‘Fendeca’ cultivars are emerged (43–46 t ha-1). Furthermore they reached also excellent fruit quality (70–75 mm diameter). The fruit quality of the ‘Galaval’ is also optimal, but the yields are notably smaller. The ‘Jugala’ produced lower yields and the coloration of the variety is also insufficient. In the case of the ‘Schniga’ the excessive increasing yields can cause quality loss easily.